2015
DOI: 10.4236/ojvm.2015.52003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Parasitological Techniques for Diagnosing Intestinal Parasites in Dogs

Abstract: Intestinal nematodes are among the most common parasites of dogs, being Toxocara spp. and Ancylostoma spp. threats to public health due to their zoonotic potential. In this study, three parasitological diagnostic techniques for detecting the eggs/oocysts of canine intestinal parasites were evaluated. Fecal samples (n = 285) were collected from the environment (i.e. public streets, squares and homes) in Garanhuns, Pernambuco, Brazil. Samples were analyzed using the Willis-Mollay simple flotation technique, spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated a wide variation ranging from 1.2% (Castro et al, 2005) to 24.2% (Capuano and Rocha 2006) in the frequency of this nematode in fecal samples collected from the environment. This variation may occur due to the period (wet or dry) in which samples were collected, or due to the different methods of retrieval of eggs (Santana et al, 2015). It is important to highlight that Ancylostoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated a wide variation ranging from 1.2% (Castro et al, 2005) to 24.2% (Capuano and Rocha 2006) in the frequency of this nematode in fecal samples collected from the environment. This variation may occur due to the period (wet or dry) in which samples were collected, or due to the different methods of retrieval of eggs (Santana et al, 2015). It is important to highlight that Ancylostoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques most frequently used are Flotation in Saturated Sodium Chloride Solution (25), Centrifugal Flotation in Saturated Zinc Sulfate Solution (26) and Spontaneous Sedimentation (27). These techniques are used mainly due to their low cost and because they are practical and direct (13,(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that other authors have detected different results. According to Santana et al (2015), the centrifugal flotation technique showed higher sensitivity towards detecting Ancylostoma spp. and Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%